Cultivation of Wolffia globosa and its application in functional food development - Sirison, Jiraporn; Ruangsomboon, Suneerat; Jongput, Buppha; Aue-umneoy, Dusit; Tongsri, Pajongjit (My University, 2025)
This study assessed the biomass productivity, biochemical composition, and functional food potential of Wolffia globosa cultivated in four nutrient media: AB hydroponic solution, Chlorella medium, 16-16-16 fertilizer, and 16-16-16 supplemented with a vitamin B complex and FeSO4 (16-16-16-B). Cultivation was conducted for eight weeks, with biomass harvested weekly. Among the treatments, the Chlorella medium produced the greatest biomass yield (133.82–236.00 g FW tank⁻1) and daily productivity (23.90–42.14 g FW m⁻2 day⁻1), significantly surpassing the other media (p < 0.05), followed by 16-16-16-B. Medium replenishment at four weeks initially enhanced growth but was later accompanied by a decline in biomass. Biochemical analysis indicated that the Chlorella medium yielded the highest protein content (46.10 ± 0.93% DW), while the AB medium supported the greatest chlorophyll-a (4.08 ± 0.00% DW) and carbohydrate levels (37.21 ± 1.12% DW); all differences among treatments were statistically significant (p < 0.05). Considering cost-effectiveness and nutritional value, the 16-16-16-B medium was optimal for cultivating W. globosa for food applications. Dried biomass from this medium was incorporated into fresh pasta and fried sweet potato balls, significantly enhancing chlorophyll-a, carotenoids, protein, fiber, and calcium contents. Sensory evaluation using a 9-point hedonic scale showed strong consumer acceptance even at higher inclusion levels. These findings highlight the role of nutrient-enriched media, particularly 16-16-16-B, in enhancing biomass yield and nutritional quality of W. globosa, affirming its potential as a functional food ingredient. Beyond nutritional enhancement, W. globosa-based foods exhibit immunomodulatory and anticancer potential through the antioxidant activity of pigments and other bioactive compounds.
Keywords: Cultivation media; Fresh pasta; Fried sweet potato balls; Protein-enriched snack; Vitamin B complex; Wolffia globosa